Meningkatkan Kesadaran Masyarakat Tentang Pentingnya Vaksinasi di STIA Bengkulu: - Nurmailiza, Nurmailiza; Hamid, Anwar; Rahayu, Novi; Ditasman, Ditasman; Romdana, Romdana (STIA Bengkulu, 2023)
Since March 2020, there has been a spike in cases of Indonesians exposed to the Covid-19 virus, which has prompted the Indonesian government to establish various policies for handling the Covid-19 pandemic, one of which is the Covid-19 vaccination policy. The Covid-19 vaccination policy was taken by the government because it is considered as one of the solutions that can increase the immunity of the people's body so as to minimize the spread of the Covid-19 virus and can restore economic conditions which have been hampered by the existence of the Covid-19 pandemic. Vaccination is the process of giving vaccines by injection or dripping into the mouth to increase the production of antibodies to ward off certain diseases. In carrying out Community Service activities several methods are used, namely: Presentation Method. The presentation method was chosen to provide an explanation about vaccination. Question and answer method. The question and answer method is very important for the participants. This method allows students to gain insight into the importance of the COVID-19 vaccination during the current pandemic. Sharing Session About COVID-19 vaccination. This sharing session is given to the participants in providing input and guidance for the material obtained. The results of this dedication show that they are very enthusiastic about following it from start to finish.